Cellular and Behavioral Functions of fruitless Isoforms in Drosophila Courtship. - von Philipsborn, A.C.; Jörchel, S.; Tirian, L.; Demir, E.; Morita, T.; Stern, D.L.; Dickson, B.J. (Current Biology, 2014)
Male-specific products of the fruitless (fru) gene control the development and function of neuronal circuits that underlie male-specific behaviors in Drosophila, including courtship. Alternative splicing generates at least three distinct Fru isoforms, each containing a different zinc-finger domain. Here, we examine the expression and function of each of these isoforms.We show that most fru(+) cells express all three isoforms, yet each isoform has a distinct function in the elaboration of sexually dimorphic circuitry and behavior. The strongest impairment in courtship behavior is observed in fru(C) mutants, which fail to copulate, lack sine song, and do not generate courtship song in the absence of visual stimuli. Cellular dimorphisms in the fru circuit are dependent on Fru(C) rather than other single Fru isoforms. Removal of Fru(C) from the neuronal classes vAB3 or aSP4 leads to cell-autonomous feminization of arborizations and loss of courtship in the dark.These data map specific aspects of courtship behavior to the level of single fru isoforms and fru(+) cell types-an important step toward elucidating the chain of causality from gene to circuit to behavior.